ANALYSIS OF GROUNDNUT MARKETING IN LAFIA LOCAL GOVERNMENT AREA OF NASARAWA STATE, NIGERIA - Yusuf, A.T.; Salami, A.O.; Solome, F.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined groundnut marketing in Lafia Local Government Area (LGA) of Nasarawa State. A multi stage sampling procedure was used for the study. Data were collected using structured questionnaire and analysed using descriptive statistics, costs-and-returns analysis, marketing margin analysis, and OLS regression were employed. Female traders dominated (66.3%), with a mean age of 34 years and six years of marketing experience. The average marketing margin was ₦404.38 per unit (12.31%), net profit per marketer was ₦70,892.25, and return on investment stood at 14.55%. OLS results showed that quantity purchased (β = 0.612, p < 0.01), marketing experience (β = 0.183, p < 0.05), and cooperative membership (β = 0.147, p < 0.05) were significant positive determinants of net profit, while transportation cost exerted a significant negative effect (β = −0.214, p < 0.01). It is concluded that groundnut marketing in Lafia LGA is a profitable and predominantly female livelihood enterprise, with volume of purchases, marketing experience, and cooperative membership as the key drivers of profitability, while transportation cost and storage inadequacy remain critical constraints to market efficiency. The study recommends targeted investment in storage infrastructure, road rehabilitation, and cooperative strengthening to enhance market efficiency and marketer welfare.